My ripped pair of shoes / Nor Asni Syahriza Abu Hassan - Abu Hassan, Nor Asni Syahriza (Universiti Teknologi MARA Cawangan Kedah, 2022)
A compilation of poems compiled from interested 118 lecturers and academicians from UiTM and other higher learning institutions